1969
DOI: 10.1080/00288233.1969.10421219
|View full text |Cite
|
Sign up to set email alerts
|

Some sources of variation in tenderness and cooking losses in lamb and mutton

Abstract: Six experiments are reported involving 218 Southdown-Romney cross ewe and wether lambs slaughtered at either 15 weeks or 9 months of age, and 136 Romney wethers slaughtered at 16 months of age. The tenderness of the meat of these animals was assessed with a mechanical tenderometer on duplicate samples of the cooked longissimus dorsi muscle of the left side.Differences in tenderness attributable to sire and pasture type were considered. Although sire effects were not consistently significant, the moderately rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Thus Purchas et al (1969) have reported a significant correlation between slaughter sequence and meat tenderness in lambs, and sarcomere length as a measure of the degree of muscle contraction can Everitt (1972) .…”
Section: Resultsmentioning
confidence: 96%
“…Thus Purchas et al (1969) have reported a significant correlation between slaughter sequence and meat tenderness in lambs, and sarcomere length as a measure of the degree of muscle contraction can Everitt (1972) .…”
Section: Resultsmentioning
confidence: 96%